Baneswa: Innovation of Introductory Media of Javanese Culture for Children Based on Pop-Up Book - Septi Yulisetiani (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
Javanese culture is very diverse, and local wisdom is important to be preserved. Children are the next generation of the nation who need to know their culture. Implementation of the introduction of culture can be done through learning arts and culture in elementary schools. The introduction of culture to children can be done with certain media that are interesting for children. One of them is in the form of a Pop Up book which is developed according to children's development. This study discusses the development of the Baneswa Pop Up Book which is used as a medium for learning the introduction of Javanese culture through folklore, wayang art, traditional dances, batik diversity, batik writing skills, macapat songs, and Javanese letters. Media development is carried out in several stages, including Analyze, Design, Development, Implementation, and Evaluation. The Baneswa Pop Up Book was developed as a cultural learning medium for children. The design is developed with images that are equipped with an audio-visual QR Code whose use is collaborated with mobile devices. The development of a Pop Up Book that is integrated with technological developments has become an innovation of cultural recognition media. The children gave a good response. They are enthusiastic about learning and getting to know the culture.